A multilayer fiber membrane for covering hair loss areas and its preparation and application
The three-layer nanofiber membrane was prepared through electrospinning technology, which solved the problems of existing wigs and color powder products being airtight and windproof, and achieved natural beauty, comfort and efficiency of covering hair loss.
Patent Information
- Application Number
- CN202411698173.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Existing wigs and color powder products used to cover hair loss have problems such as not breathable, windproof, inconvenient use, easy to fade, fly powder, and easy to fall off when sweating.
Electrospinning technology is used to prepare a three-layer nanofiber membrane. The outer layer is a hydrophobic polymer material, the middle layer is a biocompatible polymer material with antibacterial drugs, and the inner layer is a combination of water-soluble and water-soluble materials to ensure the adhesion and breathability of the fiber membrane.
It achieves natural beauty and comfort to cover the hair loss parts, and can still be effectively attached in humid environments, improving the use effect and comfort.
Abstract
Description
Technical Field
[0001] The invention relates to the application of electrostatic spinning in the direction of beauty, and in particular to a preparation method and application of a hair loss covering fiber membrane. Background Art
[0002] Electrospinning is a method of using charged polymer solutions or melts to flow and deform in an electrostatic field, solidify through solvent evaporation or melt cooling, and thus obtain fibrous substances. Electrospinning has been widely used in the field of beauty, such as as facial masks or facial mask base fabrics, using its high specific surface area and unique properties of nanometer size to promote drug absorption, but there is no precedent for using its fiber effect to make beauty products.
[0003] About half of men over 50 have problems with thinning hair or androgenic alopecia, and about one-third of women over 30 are affected by hair loss. Currently, the main solutions to the problem of hair loss include hair transplant surgery, drug treatment with minoxidil or finasteride, or concealer creams such as wigs or colored powders. Each of these methods has its own limitations: hair transplant surgery is expensive, and severe hair loss can lead to a shortage of donor hair follicles, which can also affect the surgery. In addition, the survival rate of hair follicles needs to be guaranteed after surgery. Drug treatment is not always effective or cannot achieve acceptable results. Wigs are not breathable, windproof, and inconvenient to use. Colored powders are prone to fading and flying. Therefore, it is necessary to provide a solution for covering hair loss that is less harmful and has a certain effect. This may open up a new path for the application of nanofibers in hair loss beauty. Summary of the invention
[0004] The purpose of the present invention is to overcome the following existing disadvantages: the wig is not breathable, not windproof, inconvenient to use, etc., and the color is easily faded and the powder is easily scattered when covering with colored powder, and it is easy to fall off when sweating.
[0005] Provided are a multi-layer fiber membrane for covering hair loss areas, and a preparation method and application thereof, which provides natural, beautiful and comfortable covering and has good application effect.
[0006] The present invention achieves the above objectives through the following technical solutions:
[0007] A multi-layer nanofiber membrane obtained by electrospinning technology, the fiber membrane is divided into three layers, the outer fiber membrane is a protective layer (a layer away from the scalp when applied), the middle fiber membrane is a functional layer and the inner fiber membrane is an adhesion layer (a layer adhered to the surface of the scalp when applied);
[0008] The outer protective layer is made of hydrophobic polymer materials, which provide waterproof, dustproof and antibacterial functions to protect the scalp and fiber membrane. The middle functional layer is made of biocompatible polymer materials, embedded with antibacterial drugs to achieve continuous release of drugs. The inner adhesive layer uses a combination of water-soluble materials and water-insoluble materials to ensure that the fiber membrane can adhere to the scalp. During use, the inner fiber membrane adheres to the scalp, the middle layer continuously releases antibacterial and anti-inflammatory drugs, and the outer fiber membrane is waterproof and dustproof. When the user sweats, the water-soluble components in the inner fiber membrane will gradually dissolve. This process will not only not affect the overall structure of the fiber membrane, but will enhance its adhesion properties, so that the fiber membrane can also be attached to the skin or other target surfaces in a humid environment, thereby improving its use effect and comfort. Salicylic acid is added to the middle functional layer, which has anti-inflammatory and antibacterial effects and significantly enhances the antibacterial function of the fiber membrane. The outer layer uses hydrophobic materials and pigments, which beautify the hair loss area while blocking bacteria and waterproofing, protecting the other two layers of fiber membrane and scalp. At the same time, due to the large specific surface area and many pores of the fiber membrane, it is breathable.
[0009] In the above-mentioned multi-layer fiber membrane, the multi-layer fiber membrane comprises three layers: an inner fiber membrane, a middle fiber membrane, and an outer fiber membrane.
[0010] In the above-mentioned multi-layer fiber membrane, the inner fiber membrane is obtained by using electrospinning technology, and the preparation method of the electrospinning solution comprises the following steps:
[0011] At least one water-soluble polymer or biomacromolecule and at least one water-insoluble biomacromolecule are mixed with a solvent, and ultrasonic vibration, magnetic stirring or mechanical stirring are performed until the solution is uniform to obtain an inner layer spinning solution.
[0012] In the inner fiber membrane, the water-soluble polymer or biopolymer is selected from the group consisting of polyvinyl alcohol, polyvinyl pyrrolidone, water-soluble chitosan, polyethylene oxide, wheat protein, starch, gelatin, sodium alginate, sodium hyaluronate, or a mixture of two or more thereof;
[0013] In the inner fiber membrane, the water-insoluble polymer or biopolymer is selected from the group consisting of zein, wheat prolamin, and polyvinyl butyral, or a mixture of two or more thereof;
[0014] In the above inner fiber membrane, the solvent is selected from: ethanol or a mixture of ethanol and water in any proportion;
[0015] In the above inner fiber membrane, the mass concentration of the spinning solution is 5% to 20%.
[0016] In the above-mentioned multi-layer fiber membrane, the middle-layer fiber membrane is obtained by using electrospinning technology, and the preparation method of the electrospinning solution comprises the following steps:
[0017] (1) mixing at least one biocompatible polymer with a solvent, and performing ultrasonic oscillation, magnetic stirring, or mechanical stirring until the solution is uniform to prepare a solution A;
[0018] (2) adding salicylic acid to solution A to form solution B;
[0019] In the above-mentioned middle fiber membrane, the biocompatible polymer is selected from one or a mixture of two or more of polylactic acid, polycaprolactone, polylactic acid-glycolic acid copolymer, and chitosan;
[0020] In the above-mentioned middle fiber membrane, the solvent is dichloromethane, acetic acid or acetone;
[0021] In the above-mentioned middle fiber membrane, the mass concentration of the solution A is 3% to 25%;
[0022] In the above-mentioned middle-layer fiber membrane, the mass concentration of salicylic acid is 0.1-0.5%.
[0023] In the above-mentioned multi-layer fiber membrane, the outer fiber membrane is obtained by using electrospinning technology, and the preparation method of the electrospinning solution comprises the following steps:
[0024] (1) mixing at least one hydrophobic polymer with a solvent, and ultrasonically oscillating, magnetically stirring, or mechanically stirring until the solution is uniform to prepare a solution C;
[0025] (2) Dissolve the dye in the solvent and quickly shake until uniform to obtain solution D;
[0026] (3) mixing the solution C obtained in the above step with the solution D and rapidly performing ultrasonic vibration, magnetic stirring or mechanical stirring to form a spinning solution;
[0027] In the outer fiber membrane, the hydrophobic polymer is selected from one or a mixture of two or more of polytetrafluoroethylene, polyvinylidene fluoride, polystyrene and polymethyl methacrylate.
[0028] In the outer fiber membrane, the solvent is selected from one or a mixture of two or more of dichloromethane, N,N-dimethylacetamide, N,N-dimethylformamide, acetic acid, and ethyl acetate. In the fiber membrane, the dye is selected from one or a mixture of two or more of brilliant black, catechu black, gardenia black, pigment carbon black, cuttlefish black, plant carbon black, cocoa brown, and golden cherry brown.
[0029] In the above-mentioned fiber membrane, the mass concentration of solution C is 5% to 30%, and the mass concentration of solution D is 1% to 80%; the volume ratio of solution C to solution D is A:B = 2 to 30:1, so as to adjust the proportion of dye in the solution to make the color brighter.
[0030] In the above-mentioned fiber membrane, the inner layer, middle layer and outer layer of the multi-layer fiber membrane are all made by electrospinning technology. The spinning rate of the spinning solution ranges from 0.5 to 5 ml / h, and the spinning voltage ranges from 6 to 30 kV, so as to effectively adjust the diameter of the nanofiber to be between 100 nanometers and 800 nanometers, and the thickness to be between 10 microns and 1 mm. The spinning environment humidity is ≤50%, and the spinning environment temperature is 15 to 30°C. Excessive humidity, incomplete evaporation of the solvent, and too low or too high temperature will affect the fiber filaments of the fiber membrane and cannot be effectively filamented.
[0031] The technical solution of the present invention is specifically as follows:
[0032] A multi-layer fiber membrane for covering a hair loss area, the fiber membrane is composed of three layers of an inner fiber membrane, a middle fiber membrane and an outer fiber membrane stacked in sequence;
[0033] The inner fiber membrane is a mixture of one or more water-soluble polymers and / or biomacromolecules and one or more water-insoluble polymers and / or biomacromolecules;
[0034] The middle fiber membrane is made of a mixture of salicylic acid and one or more of biocompatible polymers;
[0035] The outer fiber membrane is formed by mixing one or more hydrophobic polymers and dyes.
[0036] Furthermore, in the inner fiber membrane: the water-soluble polymer and / or biomacromolecule is selected from: one or a mixture of two or more of polyvinyl alcohol, polyvinyl pyrrolidone, water-soluble chitosan, polyethylene oxide, wheat protein, starch, gelatin, sodium alginate, sodium hyaluronate; the water-insoluble polymer and / or biomacromolecule is selected from: one or a mixture of two or more of zein, wheat alcohol-soluble protein, polyvinyl butyral;
[0037] In the middle fiber membrane, the biocompatible polymer is selected from one or a mixture of two or more of polylactic acid, polycaprolactone, polylactic acid-glycolic acid copolymer, and chitosan;
[0038] In the outer fiber membrane: the hydrophobic polymer is selected from one or a mixture of two or more of polytetrafluoroethylene, polyvinylidene fluoride, polystyrene, and polymethyl methacrylate; the dye is selected from one or a mixture of two or more of brilliant black, catechu black, gardenia black, pigment carbon black, cuttlefish black, plant carbon black, cocoa brown, and golden cherry brown.
[0039] Further, in the inner fiber membrane, the mass ratio of (water-soluble polymer and / or biomacromolecule): (water-insoluble polymer and / or biomacromolecule) is 1:9-7:3, preferably 2:8-5:5, more preferably 3:7-5:5;
[0040] In the middle fiber membrane, the mass ratio of salicylic acid to biocompatible polymer is 0.1-0.5:5-50 (preferably 0.2:10, more preferably 0.3:20).
[0041] Furthermore, in the three layers of fiber membranes, namely the inner fiber membrane, the middle fiber membrane and the outer fiber membrane, the diameter of the nanofibers is between 100 nanometers and 800 nanometers (preferably 200 nanometers to 600 nanometers, more preferably 300 nanometers to 500 nanometers), and the thickness of each layer is between 10 micrometers and 1 millimeter (preferably 20 micrometers to 500 micrometers, more preferably 50 micrometers to 200 micrometers).
[0042] Furthermore, the inner, middle and outer fiber membranes in the multi-layer fiber membrane are all made using electrospinning technology.
[0043] 1) The production process of the inner fiber membrane spinning solution is:
[0044] Mixing water-soluble polymers and / or biomacromolecules, water-insoluble polymers and / or biomacromolecules, and solvents to prepare an inner fiber membrane spinning solution;
[0045] 2) The production process of the middle layer fiber membrane spinning solution is:
[0046] First, a biocompatible polymer is mixed with a solvent to prepare a solution A;
[0047] Then, salicylic acid is added to solution A to form solution B, i.e., the middle layer fiber membrane spinning solution;
[0048] 3) The production process of the outer fiber membrane spinning solution is:
[0049] First, a hydrophobic polymer is mixed with a solvent to prepare a solution C;
[0050] Next, a dye is taken as a solution D, or the dye is dissolved in a solvent and mixed to prepare a solution D;
[0051] Then, the solution C obtained above is mixed with the solution D to form an outer fiber membrane spinning solution;
[0052] 4) Preparation of multilayer fiber membranes by electrospinning:
[0053] The first method: first, the inner fiber membrane (first layer) is prepared by electrospinning the inner fiber membrane spinning solution; second, the middle fiber membrane (second layer) is prepared by electrospinning the liquid on the upper surface of the inner fiber membrane using the middle fiber membrane spinning solution; then, the outer fiber membrane (third layer) is prepared by electrospinning the liquid on the upper surface of the outer fiber membrane using the outer fiber membrane spinning solution;
[0054] Alternatively, the second method: first, an outer fiber membrane (first layer) is prepared by electrospinning the outer fiber membrane spinning solution; secondly, a middle fiber membrane (second layer) is prepared by spinning the middle fiber membrane through liquid electrospinning on the upper surface of the outer fiber membrane; then, an inner fiber membrane (third layer) is prepared by spinning the inner fiber membrane through liquid electrospinning on the upper surface of the outer fiber membrane.
[0055] Furthermore, in the above-mentioned fiber membrane preparation process, the inner layer, middle layer and outer layer fiber membranes in the multilayer fiber membrane are all made using electrospinning technology, the spinning rate range of the spinning solution is 0.5 to 5 ml / h (preferably 1.0 to 3.0 ml / h, more preferably 1.5 to 2.5 ml / h), and the spinning voltage range is 6 to 30 kV (preferably 15 to 25 kV, more preferably 18 to 22 kV) to effectively adjust the diameter of the nanofibers to between 100 nanometers and 800 nanometers (preferably 200 to 600 nanometers, more preferably 300 to 500 nanometers), the thickness to between 10 microns and 1 mm (preferably 20 to 500 microns, more preferably 50 to 200 microns), the spinning environment humidity is ≤50% (preferably 30% to 45%, more preferably 35% to 40%), and the spinning environment temperature is 15 to 30°C (preferably 15 to 25°C, more preferably 18 to 22°C).
[0056] Furthermore, in step 1), during the process of preparing the inner fiber membrane spinning solution:
[0057] The solvent is selected from: ethanol or a mixture of ethanol and water in any proportion, the volume concentration of ethanol in the solvent is 50%-100% (preferably 60% to 90%, more preferably 70% to 85%); the mass ratio of (water-soluble polymer and / or biomacromolecule): (water-insoluble polymer and / or biomacromolecule) is 1:9-7:3, preferably 2:8-5:5, more preferably 3:7-5:5; the mass solid content of the spinning solution (water-soluble polymer and / or biomacromolecule + water-insoluble polymer and / or biomacromolecule) is 5% to 20% (preferably 5% to 30%, more preferably 10% to 20%);
[0058] Step 2) During the preparation of the middle layer fiber membrane spinning solution:
[0059] The solvent is one or more of dichloromethane, acetic acid or acetone; the mass concentration of the biocompatible polymer in the solution A is 5% to 20% (preferably 5% to 16%, more preferably 8% to 12%); salicylic acid is 0.1-0.5% of the mass of the solution A (preferably 0.2% to 0.4%, more preferably 0.25% to 0.35%);
[0060] Step 3) During the above outer fiber membrane spinning solution preparation process:
[0061] The solvent is selected from one or a mixture of two or more of dichloromethane, N,N-dimethylacetamide, N,N-dimethylformamide, acetic acid, and ethyl acetate; the mass concentration of the hydrophobic polymer in the solution C is 3% to 25% (preferably 5% to 20%, more preferably 10% to 15%); the mass concentration of the dye in the solution D is 1% to 80% (preferably 5% to 50%, more preferably 10% to 30%); the volume ratio of solution C to solution D in the outer fiber membrane spinning solution is C:D = 2 to 30:1 (preferably 5:1 to 15:1, more preferably 8:1 to 12:1).
[0062] Furthermore, the operation process of the above step 4) can be performed directly on the hair loss area of the human scalp, and a multi-layer fiber membrane for covering the hair loss area can be formed directly on the hair loss area of the human scalp.
[0063] Further, the mixing method is one or more of shaking, ultrasonic oscillation or magnetic stirring or mechanical stirring;
[0064] Furthermore, the invention can be used as a cosmetic modification film for hair loss areas of human beings to cover hair loss areas on the human scalp.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] The nanofiber membrane with the effect of covering the hair loss area of the present invention is made by using electrostatic spinning technology. The fiber membrane is specifically divided into three layers. The main components of the spinning solution of the inner layer are polymer or biomacromolecule solution and dye, wherein the solvent of the polymer or biomacromolecule solution is ethanol or a mixture of ethanol and water in any proportion. The prepared fiber is harmless to the human body. The spinning solution of the middle layer is biocompatible material and salicylic acid, which has antibacterial and anti-inflammatory effects. The spinning solution of the outer layer is made of hydrophobic material and dye, which is waterproof and antibacterial, and also has a beautifying effect. The inner layer uses a combination of water-soluble and non-water-soluble materials, which is more convenient to fit the scalp when the scalp is slightly moist.
[0067] Compared with the common color powder cosmetics, the fiber membrane of the present invention can be attached to the scalp, will not be easily rubbed off due to daily activities, is not easy to fall off, and is not easy to rub on clothes. Nanofibers can also simulate the texture of real hair, last for a long time, and are easy to use. Compared with wigs, nanofiber membranes have large specific surface area and are rich in pores, which increase the air permeability of the covered part and are comfortable to use. The inner fiber membrane contains both water-soluble components and non-water-soluble components. When the user sweats, the water-soluble components in the inner fiber membrane will gradually dissolve. This process will not only not affect the overall structure of the fiber membrane, but will enhance its adhesion performance. This design cleverly utilizes the sweat secreted by the human body naturally, so that the fiber membrane can also be attached to the skin or other target surfaces in a humid environment, thereby improving its use effect and comfort. In addition, salicylic acid is added to the middle fiber membrane of this formula, which not only has antibacterial and anti-inflammatory effects, but also can reduce oil secretion, can help relieve skin discomfort, and reduce sensitive symptoms caused by friction or environmental stimulation.
[0068] Compared with a single spinning membrane, the multi-layer electrospun fiber membrane can independently select and optimize the function of each layer of material. The outer layer focuses on hydrophobicity and waterproof performance, the middle layer focuses on antibacterial and anti-inflammatory performance, and the inner layer focuses on air permeability and adhesion, so that the physical and chemical properties of different materials can be fully utilized and utilized without affecting each other's performance due to mixing. At the same time, the layers can complement and enhance each other's functions. The hydrophobic and waterproof layer of the outer layer can protect the antibacterial components of the middle layer from environmental influences, and the antibacterial function of the middle layer can prevent the inner layer from being contaminated. The multi-layer structure can also improve the overall mechanical strength and durability, effectively isolate the erosion of different environmental factors, and extend the service life of the fiber membrane. According to different needs, the thickness, material and spinning parameters of each layer can be adjusted to achieve a gradient distribution of material properties, flexibly respond to different application scenarios, and meet diverse needs. However, after all the required polymers are dissolved and mixed for spinning, the solvents of the materials are different, which cannot dissolve all the polymers or cause spinning to be impossible.
[0069] Use electrospinning technology to produce a fiber membrane to cover the areas of hair loss. It is low-cost, lighter, more breathable, and harmless to the human body.
[0070] The electrospinning technology is used to produce nanofibers with good covering properties. Compared with the commonly used colored powders on the market, they are not easily rubbed off and have a fiber texture close to real hair, simulating natural human hair. Edible pigments are used as dyes, which are non-toxic and harmless to the human body.
[0071] Advantages over hair transplant surgery:
[0072] 1. Non-invasive: Electrospinning membranes do not require surgery, have no trauma or recovery period, and avoid surgical risks and discomfort.
[0073] 2. Instant results: The membrane can be applied instantly, no need to wait for months to see results.
[0074] Cost-effectiveness: Hair transplant surgery is expensive, while the production cost of electrospinning membranes is relatively low and more economical.
[0075] 3. No downtime: Hair transplant surgery requires a downtime, but electrospun membranes have no such limitations, and users can resume their daily activities immediately.
[0076] Advantages over drug treatment:
[0077] 1. Instant coverage: Drug treatments usually take months to work, while electrospun membranes can instantly cover areas of hair loss.
[0078] 2. No side effects: Drug treatment may have side effects (such as hormone imbalance, skin irritation, etc.), while electrospun membranes mainly provide physical coverage without systemic side effects.
[0079] 3. Wide applicability: Some drugs may not be suitable for all people (such as pregnant women or patients with certain chronic diseases), while electrospun membranes are suitable for almost all people.
[0080] Advantages over wigs:
[0081] 1. Breathability: The high porosity of the electrospun membrane makes it more breathable than a wig, more comfortable to wear, and less likely to cause stuffiness and sweating on the scalp.
[0082] 2. Natural appearance: The spunbond membrane can fit the scalp better, providing a more natural appearance that is not easily noticed.
[0083] 3. Lightweight: Spunbond membranes are lightweight and more comfortable to wear, unlike wigs which may feel heavy and uncomfortable.
[0084] Advantages over hairline powder:
[0085] 1. Durability: The electrospun membrane is more durable than hairline powder and is not easy to fall off during exercise or sweating.
[0086] 2. Easy to clean: Hairline powder can easily stain clothes and scalp, while electrospinning membrane is cleaner and less likely to fall off.
[0087] 3. No residue: Hairline powder may leave residue that is difficult to clean thoroughly, while the spinning membrane can be easily removed after use without any residue problem.
[0088] The beneficial effects of the present invention are specifically:
[0089] 1. Electrospinning technology can precisely control the diameter of the fiber and the thickness of the membrane, thereby producing a fiber membrane with specific physical and mechanical properties. It can ensure the breathability and comfort of the membrane.
[0090] 2. The nanofiber membrane produced by electrospinning has a high surface area and porosity, which helps to improve breathability while also effectively covering the hair loss areas and providing a natural appearance.
[0091] 3. High porosity can also promote the breathability of the scalp, reduce the problems of stuffiness and sweat accumulation, and thus improve wearing comfort.
[0092] 4. The color, thickness and other characteristics of the outer fiber membrane can be adjusted according to the user's needs to ensure it perfectly matches natural hair.
[0093] 5. The hydrophobic and antibacterial properties of the outer material provide dual protection of waterproof and antibacterial, enhance the protective ability of the fiber membrane, and are suitable for various harsh environments.
[0094] 6. The antibacterial function of the middle layer has the effect of sustained drug release, antibacterial and anti-inflammatory, and enhances the comfort and safety of the fiber membrane.
[0095] 7. The high air permeability and adhesion of the inner material ensure the comfort of the fiber membrane during use, avoid stuffiness and discomfort, and improve user experience.
[0096] 8. Electrospinning technology can produce very fine fibers, which helps to better simulate the fineness of real hair and avoid unnatural appearance;
[0097] 9. The fiber membrane made by electrospinning fits the scalp better, covers the skin more naturally and is not easily noticed;
[0098] 10. The multi-layer structure design can provide protection, heat dissipation and breathability at the same time, significantly improving the user experience. Through the combination of different materials, the multi-layer structure nanofiber membrane performs well in mechanical properties, biocompatibility and functionality.
[0099] 11. It can be cut into different shapes to suit the usage area according to different usage requirements. DETAILED DESCRIPTION
[0100] Example 1
[0101] 1. Preparation of spinning solution:
[0102] (1) Preparation of inner layer spinning solution:
[0103] Weigh 10 g of zein and 2 g of polyvinyl alcohol respectively, dissolve in 88 g of an aqueous solution containing 80% ethanol by volume, seal with a sealing film, and stir magnetically for 4 hours to obtain an inner layer spinning solution for standby use.
[0104] (2) Preparation of middle layer spinning solution:
[0105] Weigh 10 g of polylactic acid, dissolve it in 90 g of dichloromethane, seal it with a sealing film, stir it magnetically for 4 hours, and after the polylactic acid is dissolved, a polylactic acid solution is obtained; weigh 0.1 g of salicylic acid, dissolve it in the polylactic acid solution, stir it magnetically evenly, and obtain a middle-layer spinning solution for standby use.
[0106] (3) Preparation of outer layer spinning solution:
[0107] a. Weigh 8g of polystyrene, dissolve in 87g of N,N-dimethylformamide, seal with sealing film, stir magnetically for 4h to obtain a polymer solution, set aside;
[0108] b. Weigh 2g of melanin and dissolve it in 3g of N,N-dimethylformamide. Rapidly ultrasonicate for 10 minutes to obtain a uniform solution. Add the polymer solution obtained in step a to this solution (N,N-dimethylformamide solution of melanin) and continue to stir magnetically until uniform to obtain a spinning solution dyed black for standby use.
[0109] 2. Preparation of fiber membrane:
[0110] The inner layer spinning solution, the middle layer spinning solution and the outer layer spinning solution obtained in step 1 are subjected to electrospinning:
[0111] (1) The inner layer electrospinning solution was loaded into a 10 mL syringe, and electrospinning was performed under the parameters of voltage 12 kV, flow rate 1.2 mL / h, receiving distance 11 cm, collection drum speed 80 rpm, drum diameter 10 cm, spinning time about 1.5 hours, to obtain a uniform nanofiber inner layer fiber membrane with a diameter of about 100 nm to 200 nm and a thickness of about 80 μm to 100 μm. The spinning environment humidity was 30% and the spinning environment temperature was 15 °C.
[0112] (2) The middle layer electrospinning solution was loaded into a 10 mL syringe, the voltage was 15 kV, the flow rate was 0.8 mL / h, the receiving distance was 15 cm, and electrospinning was performed on the prepared inner layer fiber membrane for 2.25 hours to obtain a uniform fiber diameter of about 150 nm to 300 nm and a thickness of about 80 μm to 100 μm. The spinning environment humidity was 30% and the spinning environment temperature was 15 °C.
[0113] (3) The outer layer spinning solution was loaded into a 10 mL syringe and electrospinning was performed under the parameters of voltage 18 kV, flow rate 1 mL / h, and receiving distance 15 cm. Electrospinning was performed on the prepared middle layer fiber membrane for about 1.8 hours to obtain a uniform outer layer fiber membrane with a fiber diameter of about 100 nm to 300 nm and a thickness of about 80 to 110 nm. The spinning environment humidity was 30% and the spinning environment temperature was 15 °C.
[0114] Example 2
[0115] 1. Preparation of spinning solution:
[0116] (1) Preparation of inner layer spinning solution:
[0117] Weigh 8 g of polyvinyl butyral and 2 g of polyvinyl pyrrolidone respectively, dissolve them in 90 g of anhydrous ethanol, seal with a sealing film, and stir magnetically for 4 hours to obtain an inner layer spinning solution for standby use.
[0118] (2) Preparation of middle layer spinning solution:
[0119] Weigh 8 g of chitosan, dissolve it in 92 g of acetic acid, seal it with a sealing film, stir it magnetically for 4 hours, and after the chitosan is dissolved, obtain a chitosan solution; weigh 0.1 g of salicylic acid, dissolve it in the chitosan solution, stir it magnetically evenly, and obtain a middle-layer spinning solution for standby use.
[0120] (3) Preparation of outer layer spinning solution:
[0121] a. Weigh 10g of polyvinyl butyral, dissolve in 85g of anhydrous ethanol, seal with sealing film, stir magnetically for 4h to obtain a polymer solution, set aside;
[0122] b. Weigh 2g of catechu black, dissolve it in 3g of anhydrous ethanol, and quickly ultrasonically vibrate for 10 minutes to obtain a uniform solution. Add the polymer solution obtained in step a to this solution (anhydrous ethanol solution of catechu black), continue magnetic stirring until uniform, and obtain a spinning solution dyed black for standby use.
[0123] 2. Preparation of fiber membrane:
[0124] The inner layer spinning solution, the middle layer spinning solution and the outer layer spinning solution obtained in step 1 are subjected to electrospinning:
[0125] (1) The inner electrospinning solution was loaded into a 5 ml syringe and spun for about 5 minutes using a handheld electrospinning device at a voltage of 8 kV, a flow rate of 1 mL / h, and a receiving distance of 10 cm to obtain a uniform inner fiber membrane with a fiber diameter of about 300 nm to 800 nm and a thickness of about 10 to 20 μm, covering the hair loss area;
[0126] (2) The middle layer electrospinning solution was loaded into a 5 ml syringe, the voltage was 15 kV, the flow rate was 0.8 mL / ml, the receiving distance was 10 cm, and electrospinning was performed on the upper surface of the prepared inner layer fiber membrane for about 5 minutes to obtain a uniform fiber diameter of about 200 nm to 500 nm and a thickness of about 8 to 15 μm.
[0127] (3) The outer layer spinning solution was loaded into a 5 mL syringe and electrospinning was performed under the parameters of voltage 8 kV, flow rate 1 mL / h, and receiving distance 10 cm. Electrospinning was performed on the upper surface of the prepared middle layer fiber membrane for about 7 minutes to obtain a uniform outer layer fiber membrane with a fiber diameter of approximately 300 nm to 800 nm and a thickness of approximately 20 to 30 μm. The spinning environment humidity was 35% and the spinning environment temperature was 28 °C.
[0128] Example 3
[0129] 1. Preparation of spinning solution:
[0130] (1) Preparation of inner layer spinning solution:
[0131] Weigh 4 g of polyvinyl butyral and 1 g of polyvinyl alcohol respectively, dissolve them in 95 g of an aqueous solution containing 80% ethanol by volume, seal with a sealing film, and stir magnetically for 4 hours to obtain an inner layer spinning solution for standby use.
[0132] (2) Preparation of middle layer spinning solution:
[0133] Weigh 5 g of polycaprolactone, dissolve it in 95 g of acetone, seal it with a sealing film, and stir it magnetically for 4 hours. After the polycaprolactone is dissolved, a polycaprolactone solution is obtained; weigh 0.1 g of salicylic acid, dissolve it in the polycaprolactone solution, stir it magnetically evenly, and obtain a middle-layer spinning solution for standby use.
[0134] (3) Preparation of outer layer spinning solution:
[0135] a. Weigh 5g of polyvinylidene fluoride, dissolve in 90g of N,N-dimethylformamide, seal with sealing film, stir magnetically for 4h to obtain a polymer solution, set aside;
[0136] b. Weigh 2g of melanin and dissolve it in 3g of N,N-dimethylformamide. Rapidly ultrasonicate for 10 minutes to obtain a uniform solution. Add the polymer solution obtained in step a to this solution (N,N-dimethylformamide solution of melanin) and continue to stir magnetically until uniform to obtain a spinning solution dyed black for standby use.
[0137] 2. Preparation of fiber membrane:
[0138] The inner layer spinning solution, the middle layer spinning solution and the outer layer spinning solution obtained in step 1 are subjected to electrospinning:
[0139] (1) The inner layer electrospinning solution was loaded into a 10 mL syringe, and electrospinning was performed under the following parameters: voltage 12 kV, flow rate 0.8 mL / h, receiving distance 12 cm, collection drum speed 80 rpm, drum diameter 10 cm, spinning time about 1.5 hours, to obtain a uniform inner layer fiber membrane with a fiber diameter of about 200 to 500 nm and a thickness of about 20 to 30 μm;
[0140] (2) The middle layer electrospinning solution was loaded into a 10 mL syringe, the voltage was 16 kV, the flow rate was 1 mL / h, the receiving distance was 16 cm, and electrospinning was performed on the upper surface of the prepared inner layer fiber membrane for about 1 hour to obtain a uniform fiber diameter of about 400 nm to 800 nm and a thickness of about 10 μm to 15 μm.
[0141] (3) The outer layer spinning solution was loaded into a 10 mL syringe and electrospinning was performed under the parameters of voltage 20 kV, flow rate 1 mL / h, and receiving distance 15 cm. Electrospinning was performed on the upper surface of the prepared middle layer fiber membrane for about 1 hour to obtain a uniform outer layer fiber membrane with a fiber diameter of about 200 nm to 400 nm and a thickness of about 10 to 15 nm. The spinning environment humidity was 30% and the spinning environment temperature was 25 °C.
[0142] Example 4
[0143] 1. Preparation of spinning solution:
[0144] (1) Preparation of inner layer spinning solution:
[0145] Weigh 9 g of zein and 1 g of polyvinyl alcohol respectively, dissolve in 200 g of an aqueous solution containing 50% ethanol by volume, seal with a sealing film, and stir magnetically for 4 hours to obtain an inner layer spinning solution for standby use.
[0146] (2) Preparation of middle layer spinning solution:
[0147] Weigh 3 g of chitosan, dissolve it in 97 g of acetic acid, seal it with a sealing film, stir it magnetically for 4 hours, and after the chitosan is dissolved, obtain a chitosan solution; weigh 0.2 g of salicylic acid, dissolve it in the polylactic acid solution, stir it magnetically evenly, and obtain a middle-layer spinning solution for standby use.
[0148] (3) Preparation of outer layer spinning solution:
[0149] a. Weigh 4 g of polystyrene, dissolve in 76 g of N, N-dimethylformamide, seal with sealing film, stir magnetically for 4 h to obtain a polymer solution, set aside;
[0150] b. Weigh 0.4g of melanin and dissolve it in 39.6g of N,N-dimethylformamide. Rapidly ultrasonicate for 10 minutes to obtain a uniform solution. Add the polymer solution obtained in step a to this solution (N,N-dimethylformamide solution of melanin) and continue to stir magnetically until uniform to obtain a spinning solution dyed black for standby use.
[0151] 2. Preparation of fiber membrane:
[0152] The inner layer spinning solution, the middle layer spinning solution and the outer layer spinning solution obtained in step 1 are subjected to electrospinning:
[0153] (1) The inner layer electrospinning solution was loaded into a 10 mL syringe, and electrospinning was performed under the parameters of voltage 10 kV, flow rate 0.5 mL / h, receiving distance 11 cm, collection drum speed 80 rpm, drum diameter 10 cm, spinning time about 1.5 hours, to obtain a uniform nanofiber inner layer fiber membrane with a diameter of about 100 nm to 200 nm and a thickness of about 80 μm to 100 μm. The spinning environment humidity was 50% and the spinning environment temperature was 30 °C.
[0154] (2) The middle layer electrospinning solution was loaded into a 10 mL syringe, the voltage was 10 kV, the flow rate was 0.5 mL / h, the receiving distance was 15 cm, and electrospinning was performed on the prepared inner layer fiber membrane for about 2.25 hours to obtain a uniform fiber diameter of about 150 nm to 300 nm and a thickness of about 80 μm to 100 μm. The spinning environment humidity was 50% and the spinning environment temperature was 30 °C.
[0155] (3) The outer layer spinning solution was loaded into a 10 mL syringe and electrospinning was performed under the parameters of voltage 10 kV, flow rate 0.5 mL / h, and receiving distance 15 cm. Electrospinning was performed on the prepared middle layer fiber membrane for 1.8 hours to obtain a uniform outer layer fiber membrane with a fiber diameter of approximately 100 nm to 300 nm and a thickness of approximately 80 to 110 nm. The spinning environment humidity was 50% and the spinning environment temperature was 30 °C.
[0156] Example 5
[0157] 1. Preparation of spinning solution:
[0158] (1) Preparation of inner layer spinning solution:
[0159] Weigh 3 g of zein and 7 g of polyvinyl alcohol respectively, dissolve in 10 g of an aqueous solution containing 100% ethanol by volume, seal with a sealing film, and stir magnetically for 4 hours to obtain an inner layer spinning solution for standby use.
[0160] (2) Preparation of middle layer spinning solution:
[0161] Weigh 30g of polylactic acid, dissolve it in 70g of dichloromethane, seal it with a sealing film, stir it magnetically for 4 hours, and after the polylactic acid is dissolved, obtain a polylactic acid solution; weigh 0.5g of salicylic acid, dissolve it in the polylactic acid solution, stir it magnetically evenly, and obtain a middle-layer spinning solution for standby use.
[0162] (3) Preparation of outer layer spinning solution:
[0163] a. Weigh 45g of polystyrene, dissolve in 45g of N,N-dimethylformamide, seal with sealing film, stir magnetically for 4h to obtain a polymer solution, set aside;
[0164] b. Weigh 4g of melanin and dissolve it in 1g of N,N-dimethylformamide. Rapidly ultrasonicate for 10 minutes to obtain a uniform solution. Add the polymer solution obtained in step a to this solution (N,N-dimethylformamide solution of melanin) and continue to stir magnetically until uniform to obtain a spinning solution dyed black for standby use.
[0165] 2. Preparation of fiber membrane:
[0166] The inner layer spinning solution, the middle layer spinning solution and the outer layer spinning solution obtained in step 1 are subjected to electrospinning:
[0167] (1) The inner layer electrospinning solution was loaded into a 10 mL syringe, and electrospinning was performed under the following parameters: voltage 30 kV, flow rate 5 mL / h, receiving distance 11 cm, collection drum speed 80 rpm, drum diameter 10 cm, spinning time about 1.5 hours, to obtain a uniform nanofiber inner layer fiber membrane with a diameter of about 100 nm to 200 nm and a thickness of about 80 μm to 100 μm. The spinning environment humidity was 45% and the spinning environment temperature was 25 °C.
[0168] (2) The middle layer electrospinning solution was loaded into a 10 mL syringe, the voltage was 30 kV, the flow rate was 5 mL / h, the receiving distance was 15 cm, and electrospinning was performed on the prepared inner layer fiber membrane for about 2.25 hours to obtain a uniform fiber diameter of about 150 nm to 300 nm and a thickness of about 80 μm to 100 μm. The spinning environment humidity was 45% and the spinning environment temperature was 25 °C.
[0169] (3) The outer layer spinning solution was loaded into a 10 mL syringe and electrospinning was performed under the parameters of voltage 30 kV, flow rate 5 mL / h, and receiving distance 15 cm. Electrospinning was performed on the prepared middle layer fiber membrane for 1.8 hours to obtain a uniform outer layer fiber membrane with a fiber diameter of approximately 100 nm to 300 nm and a thickness of approximately 80 to 110 nm. The spinning environment humidity was 45% and the spinning environment temperature was 25 °C.
[0170] Comparative Example 1:
[0171] 1. Preparation of spinning solution:
[0172] (1) Weigh 10 g of polyvinyl alcohol (PVA) and dissolve it in 88 g of ultrapure water. Seal the container with a sealing film and stir it magnetically for 4 h to obtain a polymer solution for later use.
[0173] (2) Weigh 0.1 g of salicylic acid and dissolve it in the polymer solution prepared in step (1).
[0174] (3) Weigh 1 g of catechu black, dissolve it in 1 g of ultrapure water, and rapidly ultrasonicate for 10 minutes to obtain a uniform solution. Add the solution obtained in step (2) to this solution (catechu black aqueous solution), continue magnetic stirring until uniform, and obtain a spinning solution dyed black.
[0175] 2. Preparation of fiber membrane:
[0176] The mixed spinning solution obtained in step 1 is loaded into a 10 mL syringe, and electrospinning is performed under the parameters of voltage 20 kV, flow rate 1 mL / h, receiving distance 15 cm, collection drum speed 80 rpm, drum diameter 10 cm, and spinning time of about 4 hours to obtain a uniform fiber membrane with a fiber diameter of about 200 to 500 nanometers and a thickness of about 20 to 40 microns;
[0177] Comparative Example 2:
[0178] 1. Preparation of spinning solution:
[0179] (1) Preparation of inner layer spinning solution:
[0180] Weigh 4 g of polyvinyl butyral and 1 g of polyvinyl alcohol respectively, dissolve them in 95 g of an aqueous solution containing 80% ethanol by volume, seal with a sealing film, and stir magnetically for 4 hours to obtain an inner layer spinning solution for standby use.
[0181] (2) Preparation of outer layer spinning solution:
[0182] a. Weigh 5g of polyvinylidene fluoride, dissolve in 90g of N,N-dimethylformamide, seal with sealing film, stir magnetically for 4h to obtain a polymer solution, set aside;
[0183] b. Weigh 2g of melanin and dissolve it in 3g of N,N-dimethylformamide. Rapidly ultrasonicate for 10 minutes to obtain a uniform solution. Add the polymer solution obtained in step a to this solution (N,N-dimethylformamide solution of melanin) and continue to stir magnetically until uniform to obtain a spinning solution dyed black for standby use.
[0184] 2. Preparation of fiber membrane:
[0185] The inner layer spinning solution and the outer layer spinning solution obtained in step 1 are subjected to electrospinning:
[0186] (1) The inner layer electrospinning solution was loaded into a 10 mL syringe, and electrospinning was performed under the following parameters: voltage 12 kV, flow rate 0.8 mL / h, receiving distance 12 cm, collection drum speed 80 rpm, drum diameter 10 cm, spinning time about 1.5 hours, to obtain a uniform inner layer fiber membrane with a fiber diameter of about 200 to 500 nm and a thickness of about 20 to 30 μm;
[0187] (2) The outer layer spinning solution was loaded into a 10 mL syringe and electrospinning was performed under the parameters of voltage 20 kV, flow rate 1 mL / h, and receiving distance 15 cm. Electrospinning was performed on the prepared inner layer fiber membrane for about 1 hour to obtain a uniform outer layer fiber membrane with a fiber diameter of about 200 nm to 400 nm and a thickness of about 10 to 15 nm.
[0188] Adhesion (peel strength) test experiment:
[0189] The nanofiber membranes prepared in the above Examples 1-5 and Comparative Examples 1-2 were tested for adhesion at room temperature and humid conditions of 25°C by the following experimental steps:
[0190] Wetting agent: physiological saline, used to simulate a humid environment.
[0191] Experimental steps:
[0192] 1. Prepare nanofiber membrane samples:
[0193] (1) Collect the prepared nanofiber membrane samples.
[0194] (2) Cut the samples into pieces of size such as 3 cm × 10 cm, ensuring that all samples are of the same size.
[0195] 2. Peel strength test: (1) Peel strength in dry state: Use a pharmaceutical packaging performance tester to measure the peel strength in dry state. Record the initial peel strength.
[0196] (2) Peel strength in wet state: The nanofiber membrane sample was evenly wetted with physiological saline to simulate a humid environment. The sample was kept in a wet state for 30 minutes to ensure complete wetting. In the wet state, the peel strength was measured again using the medical packaging performance tester, and the adhesion in the wet state was recorded.
[0197] Peel strength: Peel strength is tested with a universal tensile testing machine, and the standard adopted is "GB / T1040.32-2006 Test for tensile properties of plastics".
[0198] 3. Calculation of peel strength retention rate:
[0199] Calculate the peel strength retention rate ARR:
[0200] ARR = (Fwet / Fdry) × 100%
[0201] Peel strength retention rate in wet state = [peel strength after wet treatment / initial peel strength] × 100%
[0202] Results and analysis:
[0203] The experimental results show that the nanofiber membranes prepared by the above embodiments still have good adhesion when wet, while Example 1, Example 2 and Example 3 still have good adhesion, while Comparative Example 1 uses a water-soluble material that dissolves in water and has no measurable adhesion. Although Comparative Example 2 also has a certain adhesion, it is lower than the adhesion rate of the three-layer membrane, indicating that the fiber membrane of the present invention lacks a layer, which will affect the adhesion effect.
[0204] Experimental data show that the electrospun fiber membrane of the present invention still has significant adhesion under humid conditions, which means that even in a humid environment, the electrospun fiber membrane of the present invention can still effectively adhere to the skin surface and maintain its functions and performance.
[0205] Compared with hairline powder, the invention is easy to clean and can be torn off by hand. In addition, it is not easy to dirty other parts that do not need to be covered when used.
[0206] Heat dissipation effect experiment:
[0207] The fiber diameter of the electrospun fiber membrane of the present invention is 200-800 nanometers, the pore size is 100-500 nanometers, and the porosity is 60-70%. Due to the higher porosity and smaller fiber diameter, when the fiber membrane is used on the skin surface, the sweat on the skin surface can be first absorbed by the fiber membrane as a whole, and then due to the capillary effect generated by the holes inside the fiber and the pores between the fibers, the water is adsorbed and diffused in the fiber membrane, so that the water migrates to the surface of the fiber membrane, and the adsorbed water can be discharged to the surface of the fabric as much as possible, and the water is evaporated under the action of body temperature to keep it dry. The recovery of the dry state of the fiber membrane under room temperature is tested as follows:
[0208] Experimental materials and equipment:
[0209] Fiber membrane samples: fiber membranes of different embodiments and comparative examples.
[0210] Artificial sweat: simulated sweat was prepared according to the method for preparation of acidic artificial sweat in 8.1 of GB / T 38403.2-2024 Determination of mildew inhibitors for leather and fur - Part 2: Liquid chromatography (artificial sweat extraction).
[0211] Electronic balance: used to accurately measure the mass change of a sample.
[0212] Temperature and humidity control box: used to control the temperature and humidity of the experimental environment and simulate the human scalp environment.
[0213] Timer: used to record evaporation time.
[0214] Experimental procedures
[0215] 1. Sample Preparation
[0216] Cutting samples: Cut the fiber membrane into a consistent size of 5 cm × 5 cm.
[0217] 2. Absorb sweat
[0218] Initial weighing: Weigh the initial mass of the dry fiber membrane (M_initial).
[0219] Sweat absorption: Immerse the membrane sample in artificial sweat for about 5 minutes to ensure sufficient absorption.
[0220] Remove excess liquid: Gently shake off or use absorbent paper to remove excess liquid on the surface.
[0221] Weighing after adsorption: record the mass of the sample after adsorption of sweat (M_wet).
[0222] 3. Evaporation experiment
[0223] Environment setting: Place the sample in a temperature and humidity control box to simulate the scalp environment (37°C, 50% RH (relative humidity 50%)).
[0224] Record the evaporation process: take out samples and weigh them every 5 minutes, record the mass change, pay special attention to the rapid evaporation stage in the first 20 minutes, and observe for a total of 50 minutes.
[0225] Detection time point:
[0226] First 20 minutes: record the mass change and observe the rapid evaporation process of sweat.
[0227] Last 15 minutes: Continue to record the mass change until the sample mass is close to the initial state to determine the complete evaporation time of the remaining sweat.
[0228] The complete evaporation time for each sample is as follows:
[0229] The experiment shows that after absorbing sweat, the fiber membranes of Examples 1 to 3 and Comparative Example 2 return to a nearly dry state within about 35 minutes, most of the sweat evaporates quickly within the first 20 minutes, and the remaining small amount of sweat evaporates completely within the next 15 minutes; while Comparative Example 1, due to the use of water-soluble materials, has already dissolved in the sweat absorption step. In addition, the high porosity in the fiber allows air to circulate freely, avoiding the stuffiness and discomfort caused by the wig, and the user can feel comfortable and cool all day long.
[0230] Due to the special material and structure of the electrospun membrane, it has excellent heat dissipation performance. Compared with traditional wigs, the electrospun membrane can dissipate heat more effectively and avoid overheating of the scalp. The following experiments are used to verify the heat dissipation effect of the electrospun fiber membrane of the present invention and the traditional wig:
[0231] Experimental materials and equipment
[0232] Electrospun membrane samples: nanofiber membranes of the present invention.
[0233] Traditional wig sample: Commercially available Yao Qianqian brand wig (8*10 upgraded U-shaped hand-pin-35cm-natural color).
[0234] Simulated skin device: Robert thermal manikin (Litai Technology).
[0235] Timer: record the experimental time.
[0236] Experimental procedures
[0237] 1. Sample Preparation
[0238] Electrospun membrane samples: The prepared electrospun membranes were cut into sizes matching the simulated skin device.
[0239] Traditional wig sample: Cut the sample to the same size as the simulated skin device.
[0240] 2. Simulated Skin Device Setup
[0241] Temperature setting: The temperature of the simulated skin device is set to 37°C to simulate the temperature of the human scalp when in use.
[0242] Stabilize temperature: Start the temperature controller and allow the simulated skin device to reach the set temperature and stabilize.
[0243] 3. Experimental Group Setup
[0244] Electrospinning membrane group:
[0245] The electrospun membrane sample was covered on the simulated skin preheated to 37°C, and the heating was stopped after the temperature was kept stable, and the heat dissipation rate was monitored. The thermal imaging device (Dali Technology, VD381NT online temperature measurement module) was started to record the temperature distribution and changes within 5 minutes after the membrane sample was covered.
[0246] Traditional wig set:
[0247] Under the same conditions, the traditional wig sample was covered on another simulated skin, preheated to 37°C, and the heating was stopped after the temperature was kept stable, and the heat dissipation rate was monitored.
[0248] Start the thermal imaging device to record the temperature distribution and changes after the wig sample is covered.
[0249] 4. Data Analysis:
[0250] A thermal imaging image was collected every 1 minute until the end of the experiment 10 minutes later. The thermal imaging data was exported and the average heat dissipation rate of the sample during the experiment was calculated. The experimental results are as follows:
[0251] Experimental results show that the heat dissipation effect of electrospinning membrane is significantly better than that of traditional wigs.
[0252] According to YY / T 0471.2-2004 Test Methods for Contact Wound Dressings Part 2 Water Vapor Transmission Rate of Breathable Film Dressings, 3.3 Water Vapor Transmission Rate of Wound Dressings in Liquid Contact, take six clean dry cylinders: made of corrosion-resistant material, with an inner diameter of (35.7 ± 0.1) mm (cross-sectional area of 10 cm 2 ), with a flange at each end, each of which can hold 20 mL of deionized water. One end of the cylinder is a ring-shaped clamp with an opening area of 10 cm 2 ; At the other end of the cylinder is a metal cover plate with a diameter equal to that of the flange, and a sealing ring is provided to ensure effective sealing with the flange, and both ends of the cover plate are clamped to the flange. The cylinder is placed in an incubator, which is equipped with circulating air and can maintain the temperature at (37±1)°C, so that the air is evenly distributed. During the entire test, the relative humidity (RH) is kept below 20%. The flange of the clamping plate at one end of the cylinder is used as a template to cut off the electrospinning membranes prepared in Examples 1-3 and Comparative Examples 1-2 as samples. Sufficient water is added at room temperature so that the air gap between the liquid surface and the placed sample is (5±1) mm, and the cut circular sample is accurately covered on the flange of the test container. Clamp the sample without deforming it, and form a water seal between the clamping plate and the cover plate to ensure complete sealing. Repeat this step 4 times, and prepare 5 parallel samples for each sample to calculate the average value. Weigh and record the mass of the container, sample and liquid (W 1) to 0.0001 g, place the container in an incubator with the sample facing upward and the temperature maintained at (37±1) ℃. After 24 hours, remove each container from the incubator and record the test time (T) to the nearest 5 minutes. Immediately reweigh the container, sample, and liquid and record the mass (W 2 ), accurate to 0.0001 g.
[0253] Calculate the water vapor transmission rate (MVTR) using the following formula:
[0254] X=(W 1 -W 2 ) ×1000×24 / T
[0255] Where: X-water vapor transmission rate (MVTR), unit is grams per square meter per 24 hours (g / m² / 24h);
[0256] W 1 : The mass of the container, sample and liquid, in grams (g);
[0257] W 2 : The mass of the container, sample and liquid after the test period, in grams (g);
[0258] T: test period, in hours (h).
[0259] The water vapor permeability of the electrospun membrane of the present invention and the water vapor permeability of a commercially available wig (Yao Qianqian brand 8*10 upgraded U-shaped needle-35cm-natural color) are as follows:
[0260] The experimental results show that the air permeability of the electrospun fiber membrane is significantly higher than that of a wig (Yao Qianqian brand Yao Qianqian brand 8*10 upgraded U-shaped needle-35cm-natural color). The air permeability test results show that the air permeability of the electrospun membrane of the present invention is twice as good as that of a wig. Whether in sports or high temperature environments, users can stay cool and stay away from the discomfort of sweat and stuffiness.
[0261] In addition, salicylic acid is added to the electrospun fiber membrane of the present invention, and the test is conducted according to the test method of the 6 semi-wet state (dry outside and wet inside) bacteriostatic property in Part 5 of YY / T 0471.5-2017 Test Method for Contact Wound Dressings. The difference from the document is that the test bacteria used are Gram-negative bacteria Escherichia coli and Gram-positive bacteria Staphylococcus aureus. The experimental results are as follows:
[0262] The results showed that the number of bacterial colonies after contact with the fiber membranes of Examples 1, 2 and 3 of the present invention was significantly reduced, while the fiber membrane of Comparative Example 1 had dissolved in the culture medium and had no antibacterial properties. Comparative Example 2 and the blank control group without any fiber membrane both showed obvious colony growth.
[0263] Therefore, the functions of each layer of the three-layer structure of the present invention are necessary. The single-layer structure and the double-layer structure have single functions, and it is difficult to have multiple functions such as waterproof, antibacterial, breathable and comfortable at the same time. The single-layer membrane can often only be optimized for a specific function, such as high breathability, but may lack waterproof or antibacterial properties. Although the double-layer structure can take into account two functions (such as waterproof and antibacterial), it still cannot fully cover all the required properties. As in Comparative Example 2 of the present invention, a double-layer membrane with one layer of waterproof and one layer of adhesion is insufficient in antibacterial properties. The three-layer structure can place materials with different functions in different layers, with the outer layer being waterproof, the middle layer being antibacterial and anti-inflammatory, and the inner layer being breathable and comfortable. In a single-layer or double-layer structure, these functions must be concentrated in one or two layers, which makes it difficult to optimize different functional requirements separately. The fiber membrane with a multi-layer structure can be applied to complex usage scenarios. The adaptability of a single-layer or double-layer structure in a multi-functional application scenario is poor, and it may need to be replaced more frequently or used with other products.
[0264] In general, the electrospinning membrane of the present invention is superior to traditional wigs and hairline powder in all aspects. Its lightness makes people almost feel its existence, its breathability ensures the freshness of the scalp, and its heat dissipation avoids the discomfort of stuffiness and sweat. Compared with the hairline powder, the electrospinning membrane of the present invention is more precise and clean when used. Due to its fit and fixation, the membrane only covers the hair loss parts that need to be covered and will not fall off or move at will. This not only keeps it clean, but also avoids the embarrassment that the hairline powder easily stains the face, clothes and other areas that do not need to be covered. Even after strenuous exercise or long-term wearing, the electrospinning membrane remains stable, providing users with a more secure and neat experience. All these characteristics together provide an extremely comfortable and convenient use experience, allowing users to be more confident and comfortable in daily life.
[0265] The fiber membrane of the present invention adopts electrostatic spinning technology to prepare a multi-layer fiber membrane, each layer is composed of materials with different functions to meet specific needs. The multi-layer structure design can integrate the advantages of different materials into one fiber membrane, significantly improving its comprehensive performance. The outer layer can use hydrophobic materials and pigments, the pigments are similar to hair color and have a beautifying effect, and the hydrophobic materials provide waterproof and antibacterial functions; the middle layer promotes hair follicle growth and has antibacterial and anti-inflammatory effects; the inner layer uses highly breathable and adhesive materials to ensure comfort and breathability.
Claims
1. A multi-layer fiber membrane for covering hair loss areas, characterized in that: The fiber membrane is composed of three layers of inner fiber membrane, middle fiber membrane and outer fiber membrane stacked in sequence; The inner, middle and outer fiber membranes in the multi-layer fiber membrane are all made using electrospinning technology; The inner fiber membrane is a mixture of one or more water-soluble polymers and / or biomacromolecules and one or more water-insoluble polymers and / or biomacromolecules; The middle fiber membrane is made of a mixture of salicylic acid and one or more of biocompatible polymers; The outer fiber membrane is formed by mixing one or more hydrophobic polymers and dyes.
2. The multi-layer fiber membrane for covering hair loss areas according to claim 1, characterized in that: In the inner fiber membrane: the water-soluble polymer and / or biomacromolecule is selected from: one or a mixture of two or more of polyvinyl alcohol, polyvinyl pyrrolidone, water-soluble chitosan, polyethylene oxide, wheat protein, starch, gelatin, sodium alginate, sodium hyaluronate; the water-insoluble polymer and / or biomacromolecule is selected from: one or a mixture of two or more of zein, wheat alcohol-soluble protein, polyvinyl butyral; In the middle fiber membrane, the biocompatible polymer is selected from one or a mixture of two or more of polylactic acid, polycaprolactone, polylactic acid-glycolic acid copolymer, and chitosan; In the outer fiber membrane: the hydrophobic polymer is selected from one or a mixture of two or more of polytetrafluoroethylene, polyvinylidene fluoride, polystyrene, and polymethyl methacrylate; the dye is selected from one or a mixture of two or more of brilliant black, catechu black, gardenia black, pigment carbon black, cuttlefish black, plant carbon black, cocoa brown, and golden cherry brown.
3. The multi-layer fiber membrane for covering hair loss areas according to claim 1, characterized in that: In the inner fiber membrane: the mass ratio of water-soluble polymers and / or biomacromolecules to water-insoluble polymers and / or biomacromolecules is 1:9-7:3; In the middle fiber membrane, the mass ratio of salicylic acid to biocompatible polymer is 0.1-0.5:5-50.
4. The multi-layer fiber membrane for covering hair loss areas according to any one of claims 1 to 3, characterized in that: In the three layers of fiber membranes, namely the inner fiber membrane, the middle fiber membrane and the outer fiber membrane, the diameter of the nanofibers is between 100 nanometers and 800 nanometers, and the thickness of each layer is between 10 micrometers and 1 millimeter.
5. A method for preparing a multilayer fiber film for covering hair loss areas according to claim 4, characterized in that: 1) The production process of the inner fiber membrane spinning solution is: Mixing water-soluble polymers and / or biomacromolecules, water-insoluble polymers and / or biomacromolecules, and solvents to prepare an inner fiber membrane spinning solution; 2) The production process of the middle layer fiber membrane spinning solution is: First, a biocompatible polymer is mixed with a solvent to prepare a solution A; Then, salicylic acid is added to solution A to form solution B, i.e., the middle layer fiber membrane spinning solution; 3) The production process of the outer fiber membrane spinning solution is: First, a hydrophobic polymer is mixed with a solvent to prepare a solution C; Next, a dye is taken as a solution D, or the dye is dissolved in a solvent and mixed to prepare a solution D; Then, the solution C obtained above is mixed with the solution D to form an outer fiber membrane spinning solution; 4) Preparation of multilayer fiber membranes by electrospinning: Firstly, an inner fiber membrane is prepared by electrospinning using an inner fiber membrane spinning solution; secondly, a middle fiber membrane is prepared by electrospinning on the upper surface of the inner fiber membrane using a middle fiber membrane spinning solution; then, an outer fiber membrane is prepared by electrospinning on the upper surface of the middle fiber membrane using an outer fiber membrane spinning solution.
6. The method for preparing a multilayer fiber film for covering hair loss areas according to claim 5, characterized in that: In the above-mentioned fiber membrane preparation process, the inner layer, middle layer and outer layer of the multi-layer fiber membrane are all made using electrospinning technology. The spinning rate of the spinning solution ranges from 0.5 to 5 ml / h, and the spinning voltage ranges from 6 to 30 kV, so as to effectively adjust the diameter of the nanofiber to between 100 nanometers and 800 nanometers, and the thickness to between 10 microns and 1 mm. The spinning environment humidity is ≤50%, and the spinning environment temperature is 15 to 30°C.
7. The method for preparing a multilayer fiber film for covering hair loss areas according to claim 5, characterized in that: Step 1) During the process of preparing the inner fiber membrane spinning solution: The solvent is selected from: ethanol or a mixture of ethanol and water in any proportion, the volume concentration of ethanol in the solvent is 50%-100%; the mass ratio of water-soluble polymers and / or biomacromolecules: non-water-soluble polymers and / or biomacromolecules is 1:9-7:3; the mass solid content of the spinning solution, i.e., water-soluble polymers and / or biomacromolecules + non-water-soluble polymers and / or biomacromolecules, is 5% to 20%; Step 2) During the preparation of the middle layer fiber membrane spinning solution: The solvent is one or more of dichloromethane, acetic acid or acetone; the mass concentration of the biocompatible polymer in the solution A is 3% to 25%; salicylic acid is 0.1-0.5% of the mass of the solution A; Step 3) During the above outer fiber membrane spinning solution preparation process: The solvent is selected from one or a mixture of two or more of dichloromethane, N,N-dimethylacetamide, N,N-dimethylformamide, acetic acid, and ethyl acetate; the mass concentration of the hydrophobic polymer in the solution C is 5% to 30%; the mass concentration of the dye in the solution D is 1% to 80%; and the volume ratio of solution C to solution D in the outer fiber membrane spinning solution is C:D=2 to 30:
1.
8. The method for preparing a multilayer fiber film for covering hair loss areas according to any one of claims 5 to 7, characterized in that: The operation process of the above step 4) is performed directly on the hair loss area of the human scalp, and a multi-layer fiber membrane for covering the hair loss area is formed directly on the hair loss area of the human scalp.
9. The method for preparing a multilayer fiber film for covering hair loss areas according to claim 8, characterized in that: The mixing method is one or more of shaking, ultrasonic oscillation, magnetic stirring or mechanical stirring.
10. An application of the multi-layer fiber membrane for covering hair loss areas according to claim 1, characterized in that: The invention is used as a cosmetic modification film for hair loss areas of human scalp to cover hair loss areas of human scalp.
Citation Information
Patent Citations
Bio-based polyelectrolyte complex compositions comprising non-water soluble particles
CN109689761A
Electrostatic spinning solution, artificial hair fiber and preparation method and application thereof
CN118621464A